An Investigation of High Performance Heterojunction Silicon Solar Cell Based on n-type Si Substrate - N. Memarian; M. Minbashi; M. Jalali Mehrabad (Журнал нано- та електронної фізики)
In this study, high efficient heterojunction crystalline silicon solar cells without using an intrinsic layer were systematically investigated. The effect of various parameters such as work function of transparent conductive oxide (ϕTCO), density of interface defects, emitter and crystalline silicon thickness on heterojunction silicon solar cell performance was studied. In addition, the effect of band bending and internal electric field on solar cell performance together with the dependency of cell performance on work function and reflectance of the back contact were investigated in full details. The optimum values of the solar cell properties for the highest efficiency are presented based on the results of the current study. The results represent a complete set of optimum values for a heterojunction solar cell with high efficiency up to the 24.1 % with VOC  0.87 V and JSC  32.69 mAcm – 2.